2013
DOI: 10.1109/tns.2012.2213611
|View full text |Cite
|
Sign up to set email alerts
|

3-D Spatial Resolution of 350 $\mu$m Pitch Pixelated CdZnTe Detectors for Imaging Applications

Abstract: We are currently investigating the feasibility of using highly pixelated Cadmium Zinc Telluride (CdZnTe) detectors for sub-500 μm resolution PET imaging applications. A 20 mm × 20 mm × 5 mm CdZnTe substrate was fabricated with 350 μm pitch pixels (250 μm anode pixels with 100 μm gap) and coplanar cathode. Charge sharing among the pixels of a 350 μm pitch detector was studied using collimated 122 keV and 511 keV gamma ray sources. For a 350 μm pitch CdZnTe detector, scatter plots of the charge signal of two nei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Furthermore, comparing Fig. 9 to the work of Yongzhi Yin et al in pixelated energy resolution (of which was reported to be between 9%-11%), it is evident that reading energy information from the cathode side would not only lead to an improved energy resolution, but also to greatly improved peak-to-valley and peak-to-Compton-continuum ratios, which warrants a greatly improved capability of rejecting scattered gamma rays, as well as offers an improved effective detection efficiency when a finite low-energy threshold is used [27]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, comparing Fig. 9 to the work of Yongzhi Yin et al in pixelated energy resolution (of which was reported to be between 9%-11%), it is evident that reading energy information from the cathode side would not only lead to an improved energy resolution, but also to greatly improved peak-to-valley and peak-to-Compton-continuum ratios, which warrants a greatly improved capability of rejecting scattered gamma rays, as well as offers an improved effective detection efficiency when a finite low-energy threshold is used [27]. …”
Section: Resultsmentioning
confidence: 99%
“…This is mainly due to the unrecoverable charge loss in the gap between anode pixels and the additional statistical fluctuations associated with the process of extracting the total induced signal from signals induced on adjacent pixels [27-29]. Various hardware workarounds have been implemented to improve the energy resolution.…”
Section: Challenges Of Using Small Pixel Czt and Cdte Detectors Fmentioning
confidence: 99%
“…The ENC can be calculated according to (4) and the result is given by equation (5). [See (5) at the bottom of the page.]…”
Section: B Noise Modelsmentioning
confidence: 99%
“…In [2][3], a high resolution CZT-based detector for PET is presented by C. S. Levin et al The resolution of the detectors is under mm . Moreover, PET based m pitch pixelated CZT detectors are studied in the Y.-C. Tai's team [4]. Sub-m resolution can be achieved by using such highly pixelated CZT detectors.…”
Section: Introductionmentioning
confidence: 99%
“…The resolution of the imager is under 1 mm 3 . PET based 350 μm pitch pixelated CZT detectors is studied in the Y.-C. Tai's team [4]. Sub-500 μm resolution can be achieved by using such highly pixelated CZT detectors.…”
Section: Introductionmentioning
confidence: 99%